Growth and Results of Three Varieties Celery (Apium graveolens L) With Addition of Alternative Nutrition in the Hydroponic Floating System - Eva Isnainun; Etik Wukir Tini; suwarto suwarto (Universitas Tadulako, 2021)
The objectives of the research were to determine the best varieties of celery and nutrient concentration with the addition of azolla extract for growth and yield of celery, and obtaining the best combination of varieties and nutrient concentrations for growth and yield of celery in the hydroponic floating system. The research was conducted at Screen house number A. 24 and the Laboratory of Agronomy and Horticulture, Faculty of Agriculture, Jenderal Soedirman University and was conducted from January 2020 to April 2020. The research was arranged in a two-factorial randomized block design. The first factors were varieties treatment (V): V1 (Summer variety), V2 (Amigo variety), V3 (Tall Utah variety). The second factors were treatment of nutrient concentration (K): K1 (AB mix solution 900 ppm + azolla extract 60 ml / l), K2 (AB mix solution 1100 ppm + azolla extract 60 ml / l), K3 (AB mix solution 1300 ppm + azolla extract 60 ml / l), K4 (AB mix solution 1500 ppm without azolla extract). The research variables observed were plant height, number of leaves, amount of chlorophyll, fresh root weight, dry root weight, fresh shoot weight, dry shoot weight, root length and number of stalks. The results showed that the Tall Utah variety and the nutrient concentration of 1300 ppm + 60 ml / l azolla extract was the best treatment for growth and yield of celery. The interaction between the two treatments of Tall Utah varieties and nutrient concentrations of 1300 ppm + azolla extract 60ml / l showed the best treatment on the variable number of leaves 39.16, total chlorophyll 49.91, fresh root weight 7.57 g, dry root weight 0, 73 g, dry shoot weight 2.11 g, root length 9.11 cm, and the number of petioles 8.94 pieces.